IMPROVING EDUCATION QUALITY IMPROVEMENT THROUGH ORGANIZATIONAL CULTURE - Sumarni Sumarni; Muhammad Nasir; Aldo Redho Syam; Evy Segarawati Ampry (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2021)
The research aims to describe improving the quality of higher education through organizational culture at Puanggrimaggalatung University Wajo, South Sulawesi with a sub-focus of research, namely organizational culture that has been developed at Puanggrimaggalatung University Wajo, South Sulawesi; the role of organizational culture in improving the quality of education at Puanggrimaggalatung University, Wajo, South Sulawesi; and the factors that influence the application of organizational culture atPuanggrimaggalatung University, Wajo, South Sulawesi. This study used qualitative approach with data collection techniques consisting of interviews, observations, and documentation. The data analysis technique was Miles and Huberman interactive analysis technique. This study found that improving the quality of education at Puangrimaggalatung University, Wajo, South Sulawesi through organizational culture can be seen from the development of a culture of discipline, a culture of hard work, and a culture of quality that has been going well. The organizational culture has become an effective strategy in improving the quality of education at Puangrimaggalatung University, Wajo, South Sulawesi. The role of the organizational culture of the University of Puangrimaggalatung Wajo, South Sulawesi in improving the quality of education can be seen from the implementation of a culture of discipline, and a culture of hard work carried out by campus residents, where one example is a culture of discipline, namely the discipline of lecturers in teaching, making the quality of education achievable. also with the hard work culture that has been running. In addition, the existence of a vision, mission, leadership, and competent lecturers, as well as adequate building conditions are factors that support organizational culture in improving the organizational culture of Puangrimaggalatung University, Wajo, South Sulawesi.Keywords: organizational culture, university, quality of education